1985
DOI: 10.1038/jcbfm.1985.14
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Glucose Utilization in an Experimental Brain Tumor Model by the Deoxyglucose Method

Abstract: Summary: Reevaluation of lumped and rate constants is necessary when Sokoloff's 2-deoxyglucose (DO) method is used to measure glucose utilization in pathological tissue. We describe here a modification of Sokoloff's lumped constant measurement that permits simultaneous estimation of both lumped and rate constants from a single animal experiment. A subcutaneous tumor model (AA ascites tumor) was used for measurement of these constants with a procedure similar to Sokoloff's that kept the plasma tracer concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 15 publications
(8 reference statements)
1
4
0
Order By: Relevance
“…5. with the operational equations using the K ' s deter mined from the kinetic data vs. using the literature values of the K ' s for grey matter. This is consistent with a similar demonstration by Kato et al (1985).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…5. with the operational equations using the K ' s deter mined from the kinetic data vs. using the literature values of the K ' s for grey matter. This is consistent with a similar demonstration by Kato et al (1985).…”
Section: Resultssupporting
confidence: 94%
“…The LC in malignant brain tumor tissue may not be equal to the value in normal brain tissue. Kato et al (1985) found the LC of an AA ascites flank tumor to be 0.654. Others have presented data and arguments that show that the LC is increased under conditions of hypoglycemia or ischemia, i.e., when glucose utilization is influenced more by transport limitation than by hexokinase activity (Sokoloff et aI., 1977;Crane et aI., 1983;Pardridge et aI., 1982).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In small tumors, TBF did not differ from that of surrounding brain tissue whereas in large tumors it was significantly lower, especially in the center of the tumor mass [34,36,40,[42][43][44]. Tumor metabolic rates for glucose (TMRglc) have been shown to vary irrespective of tumor size: in different regions of the same tumor, TMRglc may be substantially higher, equal or lower than in normal brain tissue [34,36,37,39]. PET investigations of human brain tumors revealed that most tumors exhibit slightly lower TMRglc values than normal brain tissue with a trend towards higher values in high-grade malignant tumors [40,41,43,45].…”
Section: Discussionmentioning
confidence: 99%
“…However, the latter metabolite cannot react further according to the Embden-Meyerhof pathway, and accumulates in the cell without contributing to the glycolytic fluxes of glucose derivatives. 11 For this reason, isotope-enriched deoxyglucose molecules are currently utilized to detect pathological states by measuring the rate of glucose utilization by brain cells and tissues, [12][13][14] either by autoradiographic techniques in vitro 15 or by PET in vivo. 16 This study demonstrates the effectiveness of T-SEDOR to selectively detect the resonances of protons bound to 13 C of this substrate, while suppressing all signals due to the remaining protons, both in the sugar moiety and in other compounds present in the cells or in the medium.…”
Section: Introductionmentioning
confidence: 99%